ACTIVE FOOD PACKAGING: A BRIEF REVIEW OF BIODEGRADABLE FILMS, EDIBLE COATINGS, AND SACHETS - da Silveira, Michelle Fernandes; Rabanal, Raúl Comettant (Infarma - Ciências Farmacêuticas, 2022)
Food packaging generally consists of low-cost and non-degradable plastic materials that contribute to environmental pollution. For this reason, new food-packaging systems with good mechanical and barrier properties have been developed as an alternative to replace synthetic polymers used in food packaging. In this sense, this article briefly reviews the active packaging concept and the development of biodegradable films, edible coatings, and sachets used in food preservation. These technological innovations gained increasing importance in the food industry over the years, constituting a new paradigm in the industry, as they interact desirably with food, promoting various solutions such as: extending or maintaining the shelf life, monitoring or improving the quality and safety of food products. In addition, these innovative systems have aroused the interest of researchers for their ability to prevent deterioration and maintain the fresh aspect, firmness, and brightness of foods, making them more attractive to consumers. Several studies have shown that active packaging is an efficient system for preserving fruits and vegetables. The application of biodegradable films, edible coatings, and sachets was discussed in this work, showing the benefits of their use in various food products.